Power cable technology - Ganguli, Sushil Kumar; Kohli, Vivek (CRC Press/Taylor & Francis, 2016)
This two-volume set thoroughly details system-level design, micro design, logic verification, and testing of integrated circuits. Electronic design automation (EDA) is a category of software tools for designing electronic systems such as printed circuit boards and integrated circuits.